Letter from Rev. Bishop Morris to James Curtis Booth - Morris, Benjamin Wistar (1869)
Rev. Benjamin Wistar Morris (1819-1906) requests a travel pass from James Curtis Booth (1810-1888). Booth notes on the letter verso that he had received the request too late.
Keywords: Booth, James Curtis, 1810-1888; Morris, Benjamin Wistar, 1819-1906